The Effectiveness of CLT-Based STAD to Improve Speaking Skill of Phase F Student at Islamic Senior High School 2 Surakarta - Shofia, Arina Nuriyana; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Speaking is the skill on which students will be most evaluated in real-life situations. It's an important part of everyday interaction and more often than not, a person's first impression is based on a student's ability to express themselves fluently and understandably. This research of the objectives of this research are generally to: 1) improve the speaking skills of Phase F students through the application of the Communicative Language Teaching (CLT) Based Student Team Achievement Division (STAD)-Type method in speaking learning, 2) improve the vocabulary of Phase F students through the application of the CLT Based STAD-Type method in speaking learning, 3) increase grammar to improve speaking skills and learning achievement of Phase F students through the application of the CLT Based STAD-Type method in speaking learning. While specifically aiming to: 1) find out the results of the application of the CLT Based STAD-Type method in improving speaking ability of phase F students, 2) increase vocabulary of Phase F students, 3) increase grammar to improve speaking skills and learning achievement of Phase F students. Using experimental research for data collection is done through tests, observations, field notes and documentation. The subject of this study was conducted on grade XI or Phase F students in Independent Curriculum, as many as 36 students consisting of 24 female students and 12 male students. The results showed an increase ability and learning outcomes of speaking, in the initial condition the ability to speak English only 27.78% increase in cycle I to 69.4% and increased again in cycle II which was 83.3%. Similarly, the learning achievement in the initial condition of students was completed by 36.1% or 13 students from 36 students and increased in the cycle I to 63.8% or 23 students from 36 students and again increased in the cycle II to 80.56% or 29 students from 36 students. This research concluded that: 1) The application of the CLT Based STAD-Type method can increase to improve students' speaking skills in speaking lessons which are characterized by student activeness when learning speaking material, student awareness to memorize vocabulary to be able to express ideas to speak, students can be actively involved in speaking and answering questions in discussion and argument, 2) The application of the CLT Based STAD-Type method can improve the English learning achievement of Phase F students which can be seen from the test scores in the initial condition of the learning completeness level of 36.1% with KKM 75 with an average score of 73.00 increased in the cycle II by 80.56% with an average value of 82.00.